A morte e o homem: circum-navegações nas incertezas da vida - Bastos, Cláudio Roberto Fontana (2016)
This thesis aims at considering the “death and life” dialogy under the perspective of com-plexity. The work Humanity and death constitutes an hermeneutic part of the reading and analyses held for the understanding of the subject. Such work is not restricted to the field of thanatology and does not lose its anthropological root, as well as its reflexive condition. At first, the itinerary we followed considers the “life and death” dialogy as an embryo of the complex thinking. The dialogy of the death and its reform by means of the complex thinking are closely related to the reform of life and the reform of society. The second moment adres-ses Edgar Morin’s approach towards Paul Ricœur’s thinking. The main text is Living up to dead, posthumous manuscript, in which are the losses experiences in the author’s autobio-graphy and their influence in the building of his thinking. We developed the subjects me-mory, forgetfulness of the grief as means to a reflexion based on uncertainties and that allow the criticism and the facing of the death seen as being separate from life. The third moment points to the reflections about the afterdeath. It is about the prolongations of life, the progress of Science, the immortality, so present in Morin’s reflections, and Ricœur demonstrates, in the subjects memory, forgetfulness and grief, a way of staying alive until death. Ricœur assigns the living ones the task of accepting and spreading the will of being. In the extreme situations of horror and anguish, the retrieving of memory and history acquires strength and potentialities that go beyond the ordinary death. The themes of salvation and resurrection are treated within the Judeo-Christian view by Morin and under Ricœur’s anthropologic and hermeneutic perspective. Both believe in life and offer their own biographical notes as a Science which believes in passions, in hope and in the ethics of solidarity